2015
DOI: 10.1371/journal.pone.0117226
|View full text |Cite|
|
Sign up to set email alerts
|

An Investigation of the Endocrine-Disruptive Effects of Bisphenol A in Human and Rat Fetal Testes

Abstract: Few studies have been undertaken to assess the possible effects of bisphenol A (BPA) on the reproductive hormone balance in animals or humans with often contradictory results. We investigated possible direct endocrine disruption by BPA of the fetal testes of 2 rat strains (14.5–17.5 days post-coitum) and humans (8–12 gestational weeks) and under different culture conditions. BPA concentrations of 10-8M and 10-5M for 72h reduced testosterone production by the Sprague-Dawley fetal rat testes, while only 10-5M su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 61 publications
8
54
0
Order By: Relevance
“…Therefore, the dose of 10 -5 M of BPA, which was found to significantly inhibit testosterone here, was much higher than the concentrations recorded in the body fluids. The significant BPA-induced anti-androgenicity observed at 10 -5 M in adult human testes was consistent with that obtained with human fetal testes when cultured in the presence of trophic hormone (hCG or LH), which optimizes the organ's integrity (histology and hormone production) during the culture periods investigated both in terms of histology (Ben Maamar et al, 2015) and hormone production (Ben-Maamar et al, 2015;Eladak et al, 2015). The fact that BPA or BPA-A can impact the production of testosterone by the human fetal testis at doses lower than 10 -5 M only appeared in the absence of trophic hormones (N' Tumba-Byn et al, 2012;Ben-Maamar et al, 2015;Eladak et al, 2015).…”
Section: Inhibin Bsupporting
confidence: 75%
See 2 more Smart Citations
“…Therefore, the dose of 10 -5 M of BPA, which was found to significantly inhibit testosterone here, was much higher than the concentrations recorded in the body fluids. The significant BPA-induced anti-androgenicity observed at 10 -5 M in adult human testes was consistent with that obtained with human fetal testes when cultured in the presence of trophic hormone (hCG or LH), which optimizes the organ's integrity (histology and hormone production) during the culture periods investigated both in terms of histology (Ben Maamar et al, 2015) and hormone production (Ben-Maamar et al, 2015;Eladak et al, 2015). The fact that BPA or BPA-A can impact the production of testosterone by the human fetal testis at doses lower than 10 -5 M only appeared in the absence of trophic hormones (N' Tumba-Byn et al, 2012;Ben-Maamar et al, 2015;Eladak et al, 2015).…”
Section: Inhibin Bsupporting
confidence: 75%
“…The significant BPA-induced anti-androgenicity observed at 10 -5 M in adult human testes was consistent with that obtained with human fetal testes when cultured in the presence of trophic hormone (hCG or LH), which optimizes the organ's integrity (histology and hormone production) during the culture periods investigated both in terms of histology (Ben Maamar et al, 2015) and hormone production (Ben-Maamar et al, 2015;Eladak et al, 2015). The fact that BPA or BPA-A can impact the production of testosterone by the human fetal testis at doses lower than 10 -5 M only appeared in the absence of trophic hormones (N' Tumba-Byn et al, 2012;Ben-Maamar et al, 2015;Eladak et al, 2015). According to the human exposure studies available on BPA-A, equivalent values to those of BPA were found in urine for BPS and BPF, at average levels of about 10 -9 -10 -10 M, (Zhou et al, 2014).…”
Section: Inhibin Bsupporting
confidence: 75%
See 1 more Smart Citation
“…In a comparative study by Maamar et al (2015), the influence of BPA was studied both on rats and on human fetal testes, and it was determined that in both cases BPA had dose-dependent anti-androgenic effects. Nevertheless, the authors urge caution in interpreting the results obtained on rodents and their application in human medicine (Maamar et al 2015).…”
Section: Influences Of Bpa On Reproduction Of Malesmentioning
confidence: 99%
“…Endocrine disruptors can cause cancerous tumors, birth defects and other developmental disorders. BPA was shown to be associated with breast and prostate cancers, genital defects in males [6][7][8]. Due to possible low dose effects of unknown toxicological relevance and weekly oestrogenic BPA is the subject of many investigating assessing, its potential toxicity and human exposure for a more conclusive risk assessment [9,10].…”
Section: Introductionmentioning
confidence: 99%